An Analysis of the Main Character of Patty Jenkin's WONDER WOMAN (2017) Movie : A Psychoanalytic Approach - Ita Nur'aeni; Dila Charisma; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2021)
In general, literature is a phenomenon that is expressed through words, which in particular can be presented in the form of works in the form of movie. This study aims to determine, analyze, and describe the character and personality of the main character in the movie entitled “wonder woman” by focusing on the structure of the personality of the id, ego and super ego. This research analyzes the personality of Diana Prince as a main character of the Wonder Woman movie using Sigmund Freud's theory. This research uses a qualitative descriptive research method because the data taken come from movie scripts and movie video. The results of this study are the main character named Diana Prince has an id personality which is based on innate instincts from birth, the ego structure of Diana Prince's personality in carrying out actions according to the norms applied in society. Furthermore, the super ego shown in Diana Prince with her concern for the people around her. The personality that often appears in Diana Prince is the superego that makes her a woman by making many good contributions to be a hero in saving the world.